The Role of Egg Parasitoids to Control Rice Stem Borers (Scirpophaga incertulas) Walker (Lepidoptera: Pyralidae) in Subak Renon, Denpasar-Bali, Indonesia - Yuliadhi, Ketut Ayu; Wijaya, I Nyoman; Costa Cruz, Latizio Beni Da; Yudha, I Kadek Wisma; Utama, I Wayan Eka Karya; Cha, Joo Young (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University, 2024)
Rice stem borers are the main pest and endemic for the rice plants. The intensity of the attacks paneled fluctuating until it Reaches 90% and causes loss and it is requisite to get to pay serious attention. One of Efforts to Overcome it is the implementation of integrated pest management (IPM) through biological control by natural competitors. Research objectives is to know the role of an egg parasitoids in controlling rice yellow stem borer. Research conducted at Subak Renon, Renon Village, South Denpasar District, Denpasar Regency since April to July 2022. Research is done with the survey by truncate leaf rice containing eggs of rice stem borers at random. The sampling done every week since the plants were two weeks old in Ciherang rice plants. Identification of eggs parasitoids observed under microscope used the key determination insects (Kalshoven, 1981) and the percentage of eggs parasitoids is calculated by a formula Nishida and Torri (1970). The result showed that found three species of parasitoid eggs roomates played the role to suppress the development of yellow rice stem borer namely Trichogramma japonicum Ashm., Telenomus rowani Gahan and Tetrastichus schoenobii Ferr with parasitation capacity of 66%. The highest capacity parasitation played by T. japonicum, followed T. rowani and T. schoenobii Ferr.